2002
DOI: 10.1017/s003060530200073x
|View full text |Cite
|
Sign up to set email alerts
|

Meat prices influence the consumption of wildlife by the Tsimane' Amerindians of Bolivia

Abstract: Wildlife (bushmeat or game) is the primary game. The results indicated that the price of fish and meat from livestock is positively correlated with con-source of protein for most poor households in tropical forests, and its consumption is resulting in unsustainable sumption of wildlife, suggesting that policy makers may be able to reduce the unsustainable hunting of wildlife hunting of large animals, even in isolated regions. As a result, loss of fauna is often a more immediate and for food by reducing the pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 2 publications
6
44
0
4
Order By: Relevance
“…First, the data from Bolivia suggest that the income elasticity of fish consumption is sensitive to the year of measurement. In their comparative study with data from 1997 to 1998, Wilkie & Godoy (2001) found a statistically significant negative association between fish consumption and monetary income but the later study by Apaza et al (2002) carried out in 2000 among the Tsimane' found no such association. Second, the study of Vickers (1988) aside, none of the studies on wildlife consumption provide estimates of changes over time in wildlife consumption, and even Vickers relied on a small sample of observations (n = 6) and did not control for the role of income or other third variables.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…First, the data from Bolivia suggest that the income elasticity of fish consumption is sensitive to the year of measurement. In their comparative study with data from 1997 to 1998, Wilkie & Godoy (2001) found a statistically significant negative association between fish consumption and monetary income but the later study by Apaza et al (2002) carried out in 2000 among the Tsimane' found no such association. Second, the study of Vickers (1988) aside, none of the studies on wildlife consumption provide estimates of changes over time in wildlife consumption, and even Vickers relied on a small sample of observations (n = 6) and did not control for the role of income or other third variables.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have described Tsimane' use of game, fish and birds (Chicch´on, 1992;Apaza, 2001;P´erez, 2001;Wilkie & Godoy, 2001;Apaza et al, 2002Apaza et al, , 2003Gut´ıerrez, 2005). Besides analyzing the relation between: (1) household monetary income or household wealth; (2) wildlife consumption, the prior studies just cited make the following points that bear on this article: (a) Tsimane' use wildlife mainly for food rather than for other ends (e.g.…”
Section: Background and Study Sitementioning
confidence: 99%
See 2 more Smart Citations
“…Two kinds of poaching can be differentiated. One represents a way to procure a primary source of protein [5,38,40] and the other is dedicated to commercial activity. Large towns have proved to create high pressure hunting areas [3].…”
Section: Discussionmentioning
confidence: 99%